2013
DOI: 10.1002/ijc.28456
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐CD73 therapy impairs tumor angiogenesis

Abstract: CD73 is an ecto-nucleotidase overexpressed in various types of tumors that catabolizes the generation of extracellular adenosine, a potent immunosuppressor. We and others have shown that targeted blockade of CD73 can rescue anti-tumor T cells from the immunosuppressive effects of extracellular adenosine. Another important function of extracellular adenosine is to regulate adaptive responses to hypoxia. However, the importance of CD73 for tumor angiogenesis and the effect of anti-CD73 therapy on tumor angiogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 51 publications
4
124
0
Order By: Relevance
“…A 2A -receptor inhibition has been shown to synergize with the effect of PDL-1 immune checkpoint inhibitors in preclinical tumor models. 41 This treatment combination is currently undergoing clinical trials in numerous …”
Section: Discussionmentioning
confidence: 99%
“…A 2A -receptor inhibition has been shown to synergize with the effect of PDL-1 immune checkpoint inhibitors in preclinical tumor models. 41 This treatment combination is currently undergoing clinical trials in numerous …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that adenosine and other purines promote endothelial proliferation and migration in vitro [24,25], although results in more physiological models of sprouting angiogenesis have been contradictory [7,[26][27][28]. Therefore, we analyzed the role of extracellular purine metabolism on angio-and lymphangiogenesis using a quantitative model of sprouting [29].…”
Section: Purinergic Signaling Contributes To Angiogenesis But Not To mentioning
confidence: 99%
“…CD73 is a GPI-anchored nucleotidase that catabolizes the production of extracellular adenosine. Inspired by landmark studies from Sitkovsky and colleagues, we and others have underscored the therapeutic potential of blocking CD73 and adenosine receptors for cancer therapy (12)(13)(14)(15). In the ID8 mouse model of ovarian cancer, Zhang and colleagues reported that CD73 gene silencing, or targeted blockade of CD73 with a monoclonal antibody (mAb) or a small molecule inhibitor, enhances antitumor T-cell responses and improves animal survival (11).…”
Section: Introductionmentioning
confidence: 99%